ENGLISH LESSONS IN LOWER SECONDARY SCHOOLS IN POLAND: REFLECTIONS BASED ON LEARNER VOICES - Ellis, Melanie (Neofilolog, 2019)
This paper reports on some of the data from a large-scale study Teaching and Learning Foreign Language in lower secondary school, which began in the school year 2011-12 and traces selected groups of learners through the three years of Key Stage 3 (gimnazjum), ending in school year 2013-14. The study was conceived and is managed by the Foreign Language Section of the Educational Research Institute (ERI) in Warsaw with European funding. (see Acknowledgement). In this article the focus is on data obtained from interviews conducted with learners from class one of 120 lower secondary schools, where the students were asked to describe and give opinions about learning English in their school and to imagine an ideal lesson. The learners are the reason that lessons in school take place, but their views are rarely consulted. This study attempts to redress the balance.